“Doing good and feeling good” Relationship between authentic leadership with followers' work engagement: The mediating role of hedonic and eudaimonic wellbeing - Farid, Tahir; Iqbal, Sadaf; Basahal, Abdulrahman S.; Khattak, Amira; Khan, Muhammad Khalil; Salam, Mohammad Asif (Frontiers in Public Health, 2022)
The positive behavioral style of authentic leadership has attracted academicians' and practitioners' attention to focus more on a healthy workplace environment and its influence on followers' valued workplace relationship outcomes, such as employees' work engagement. From the lens of social exchange perspective, we tested a unified model of authentic leadership and its influence on the followers' wellbeing (hedonic and eudaimonic wellbeing) and work engagement. We also examined the mediating role of hedonic and eudaimonic wellbeing on followers' work engagement. Using a time-lagged design, we collected data from 250 telecom sector workers employed in the capital city of Islamabad, Pakistan. The results indicate the positive influence of authentic leadership on followers' work engagement and employees' hedonic and eudaimonic wellbeing. Hedonic and eudaimonic wellbeing also positively mediated the relationship between authentic leadership and followers' work engagement. The theoretical and practical implications of the study are also discussed.